2020
DOI: 10.1111/jan.14535
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intermittent Phototherapy versus Continuous Phototherapy for Treatment of Neonatal Hyperbilirubinaemia: A Systematic Review and Meta‐analysis

Abstract: Aims We review the current literatures to determine whether intermittent phototherapy is more effective than continuous phototherapy in treating neonatal hyperbilirubinaemia. Design The systematic review is a systematic review and meta‐analysis. The Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines were used for reporting methods and results of synthesis with meta‐analysis. Synthesis Without Meta‐analysis (SWIM) guidelines were used for reporting methods and results of synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Video calls alongside letters and telephone calls were reported to aid in reducing depression among nursing home residents, and were also associated with positive social interaction, decreased loneliness, and better quality of life [ 74 , 75 ]. Some video-calling modalities posed problems for older users, including auditory interference and a lack of familiarity with the technology [ 76 ], highlighting the need for the development of technology that is specifically tailored to older people. Another technology known as simulated presence therapy, whereby video messages are frequently exchanged between family and the older person, led to the enhanced well-being of residents living with dementia and decreased behavioural and psychological symptoms [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Video calls alongside letters and telephone calls were reported to aid in reducing depression among nursing home residents, and were also associated with positive social interaction, decreased loneliness, and better quality of life [ 74 , 75 ]. Some video-calling modalities posed problems for older users, including auditory interference and a lack of familiarity with the technology [ 76 ], highlighting the need for the development of technology that is specifically tailored to older people. Another technology known as simulated presence therapy, whereby video messages are frequently exchanged between family and the older person, led to the enhanced well-being of residents living with dementia and decreased behavioural and psychological symptoms [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent systematic review concluded that both intermittent and continuous PT appeared to be equally effective for treating UH. 43 El-Sakka et al 44 reported that although PT effectively decreased UCB levels in breastfed neonates, these neonates demonstrate a slower response to PT than a bottle or mixed-fed neonates. However, the result of the studies with breastfed participants in our research showed a similar reduction of TSB levels as others studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that metalloporphyrins [ 38 ], Sn-mesoporphyrin [ 11 ], ursodeoxycholic acid [ 39 ], and phenobarbital [ 40 , 41 ] have been proposed as alternative approaches for preventing or treating neonatal hyperbilirubinemia, and melatonin promotes neuroprotective brain-derived neurotrophic factor expression in neonatal hemolytic hyperbilirubinemia [ 42 ], phototherapy is the current model. Phototherapy was first introduced in 1958 for the treatment of neonatal hyperbilirubinemia [ 43 ]. In a hospital setting, the blue part of the spectrum near the wavelength peak of 460 nm, is a safe and effective treatment without major side effects [ 44 , 45 ].…”
Section: Phototherapy and Free Versus Total Bilirubinmentioning
confidence: 99%